Pengaruh Kearifan Lokal dan Kualitas Layanan Terhadap Keputusan Pembelian Melalui Harga pada Restoran Bebek Sawah di Kota Padang - Christine Dwi Hendria; Emil Salim; Sivia Sari (Jurnal Bintang Manajemen, 2025)
This research aims to find out how much influence local wisdom and service quality have on purchasing decisions with price as an intervening variable at the Bebek Sawah Restaurant in Padang City. The population in this study is unknown, therefore this study uses the ferdinant formula. and the sample used in this research was Bebek Sawah customers in Padang City, namely 68 people. The method used is Structur Equation Modeling (SEM) with Particular Least Square (PLS) 3.0. by using a questionnaire as many as 68 respondents. The results of data analysis conclude that there is a positive and significant influence of local wisdom variables on purchasing decisions. There is a positive and significant influence of service quality variables on purchasing decisions. There is a positive and significant influence of the price variable on the purchasing decision variable. There is a positive and insignificant influence of the local wisdom variable on the purchasing decision variable through the price variable as an intervening variable. There is a positive and insignificant influence of the service quality variable on the purchasing decision variable through price as an intervening variable.